Intraperitoneal allogeneic hepatocyte transplantation in rats with induced toxic liver cirrhosis (Eurasian Journal of Ecology, 2016)
Allogeneic hepatocytes were transplanted into peritoneal cavity in rats with induced toxic liver cirrhosis. Hepatocytes were found to accumulate in intestinal lymph nodes and were positively stained for Hep Par 1 marker. The whole approach improved the liver function and reduced mortality in rats with toxic liver cirrhosis.
Keywords: liver; cirrhosis; hepatocyte; cell therapy; transplantation